Enhancing the online learning experience of Chinese college students: an investigation of facilitation strategies and their mixed association with student satisfaction - Fang , Shixin; Lu , Yi; Zhang , Guijun; Qin , Wenjuan (Research in Learning Technology, 2024)
Facilitation strategies play a critical role in helping instructors teach effectively in an online environment. However, there is a lack of research on how different facilitation strategies impact the online learning experience. To address this gap, our study surveyed 5980 college students from two universities in China and analysed the associations between facilitation strategies and student satisfaction using multivariate and logistic regression analyses. Our findings reveal that facilitation strategies aimed at managerial and technical purposes have different effects on student satisfaction with instructors compared to their satisfaction with their own achievement and engagement. Additionally, we found that student group discussion had a negative association with student satisfaction, potentially due to a preference for hierarchical learning in Confucian-heritage culture. In contrast, after-class learning materials were positively associated with student satisfaction. These findings offer important implications for pedagogical practices that aim to enhance the online learning experience for Chinese students on a large scale.